Medial frontal cortex: from self-generated action to reflection on one's own performance. - Passingham, R; Bengtsson, S; Lau, H (2010)
It was suggested over 20 years ago that the supplementary motor cortex is involved in self-generated behaviour. Since then, there have been many studies using electrophysiology and brain imaging of the role of the supplementary motor cortex and anterior cingulate cortex. In light of the findings, the proposal that these regions are crucial for self-generated action has recently been challenged. Here, we review the recent literature and argue that the proposal survives the findings. We further argue that it can be generalised to cover reflection on mental states. Finally, we suggest that the pattern of anatomical connections is consistent with the proposal that the medial frontal cortex is crucially involved in self-generated action and self-reflection.